LEGAL PROTECTION FOR CHILDREN AS PERFORMANCE OF CRIMINAL ACTION - I Gusti Ayu Krisna Permata Sari (Ganesha Law Review, 2020)
Persecution is a crime that is rife lately. Perpetrators in this crime are also rife in the scope of children. The children innocently take actions that should not be carried out by children their age. For the sake of vent their emotions to hit, kick, and even hurt certain people who are around them. This is what must be addressed and searched for the cause. Because this action can have fatal consequences later for people who are affected by the persecution. But not only the victims, the perpetrators also must be corrected so that later the perpetrators do not repeat the provisions again. Not just sanctions in improving the child's psychic but also in terms of legal protection received by the child as a perpetrator in the criminal act of abuse. Legal protection is something that must be obtained by someone, either as a perpetrator or as a victim in a crime. This is in accordance with Law No. 11 of 2012 concerning the Criminal Justice System for Children. In other words the child must be treated humanely, given special facilities and infrastructure and the imposition of sanctions for the child must be adjusted to the best interests of the child.